Women in Zimunya and the musha mukadzi or umuzi ngumama philosophy for sustainable livelihoods - Chirara, Tracey (HTS teologiese studies, 2023)
The musha mukadzi (Shona) or umuzi ngumama (Ndebele) is an African gendered philosophy that means women make up the home. This philosophy has been researched in African traditional religions (ATRs) and is interrogated from interdisciplinary angles in academia. African feminist research has highlighted how this philosophy can be derogatory, stereotyped and oppressive to women if it is naïvely used in domestic contexts. As a result, contemporary African feminists and gender scholars attempt to expose both the liberative and oppressive nature of this philosophy. This study seeks to interrogate how women from the grassroots understand this philosophy. It draws from in-depth interviews with women from Zimunya, Mutare, in Zimbabwe who describe this philosophy as a resource for sustainable livelihoods. Methods used to collect data involved in-depth interviews from a sample of 10 women whose ages ranged from 35 to 50 years. The findings highlight that for both single and married women in Zimunya, the musha mukadzi or umuzi ngumama philosophy has empowering traits that enhance women’s agency and sustainable livelihoods in the domestic household. They describe how this philosophy has empowered them to initiate income-generating projects that include rearing of poultry (road runners), membership to a sewing club, selling dried traditional foods and money savings ( mikando ). Contributions: This article explores an African gendered philosophy, musha mukadzi or umuzi ngumama [women make the home], and how this has been used as a resource by women in sustaining livelihoods.